PENGEMBANGAN MEDIA PEMBELAJARAN FRACMIX BOARD UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA MATERI PECAHAN CAMPURAN - Ahmad, Nakir T; Abdullah, Gamar; Aries, Nur Sakinah; Marshanawiah, Andi; Pulukadang, Wiwy Triyanty (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
This study aims to develop an interactive learning media called Fracmix Board to improve learning outcomes of fourth-grade students at SDN 9 Telaga Biru in the topic of mixed fractions. The research employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The results showed that the Fracmix Board was highly feasible based on expert validation, with average scores of 94.7%, indicating it is highly appropriate for use. It was also found to be highly practical according to teacher and student assessments, with an average score of 95.1%. In terms of effectiveness, the N-Gain analysis yielded a score of 0.72, categorized as